Rational Adjudication in Diverse Society: Integrating Raz’s Philosophyof Authority in Indonesian Constitutional Justice - Artha Debora Silalahi; Rizal Mustansyir; Sindung Tjahyadi (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. Constitutional courts in Indonesia play a crucial role in interpreting the Constitution and safeguarding democratic principles within a pluralistic society. Joseph Raz’s philosophy of authority can strengthen this judicial practice by emphasizing rational, ethical, and public-oriented adjudication. According to Raz, legitimate authority must prioritize public welfare and align with societal values, offering a relevant framework for constitutional interpretation. In the Indonesian context, where constitutional decisions significantly impact a diverse society, Raz’s thought assists judges in navigating complex social and cultural dynamics with a reasoned and ethical approach. This philosophy is particularly relevant in addressing conflicts between legal texts and religious or cultural norms, while supporting purposive and inclusive legal interpretation. Raz’s principles advocate for a holistic approach that combines textual analysis with ethical considerations, enabling judges to formulate decisions that uphold justice and democracy. By adopting this framework, constitutional courts can become more responsive to societal needs, strengthen democratic governance, and produce decisions that address contemporary issues in Indonesia. This approach ensures judicial independence while fostering equitable and context-sensitive rulings that align with the country’s constitutional mandate and the pluralistic nature of its society.  Keywords: Joseph Raz, Philosophy of Authority, Constitutional Court, Rational Adjudication, Moral Consideration.  Abstrak. Peradilan konstitusional di Indonesia memainkan peran penting dalam menafsirkan Konstitusi dan menjaga prinsip demokrasi dalam masyarakat pluralistik. Filosofi otoritas Joseph Raz dapat memperkuat praktik peradilan ini melalui penekanan pada ajudikasi yang rasional, etis, dan berorientasi pada kepentingan publik. Menurut Raz, otoritas yang sah harus memprioritaskan kesejahteraan masyarakat dan sejalan dengan nilai-nilai sosial, sehingga menawarkan kerangka kerja yang relevan untuk interpretasi konstitusional. Dalam konteks Indonesia, di mana keputusan konstitusional berdampak luas pada masyarakat yang beragam, pemikiran Raz membantu hakim menghadapi kompleksitas sosial dan budaya dengan pendekatan berbasis alasan dan etika. Filosofi ini relevan untuk mengatasi benturan antara teks hukum dengan norma agama dan budaya, serta mendukung interpretasi hukum yang purposif dan inklusif. Prinsip Raz mendorong pendekatan holistik yang menggabungkan analisis tekstual dan pertimbangan etis, memungkinkan hakim untuk merumuskan keputusan yang mendukung keadilan dan demokrasi. Dengan mengadopsi kerangka ini, peradilan konstitusional dapat lebih responsif terhadap kebutuhan masyarakat, memperkuat tata kelola demokratis, dan menghasilkan keputusan yang relevan dengan isu-isu kontemporer di Indonesia.  Kata Kunci: Joseph Raz, Filsafat Otoritas, Peradilan Konstitusional, Ajudikasi Rasional, Pertimbangan Moral